Human factors influencing contractors' risk attitudes: a case study of the Malaysian construction industry - Taofeeq, D. M.; Adeleke, A. Q.; Ajibike, W. A. (UTS ePress, 2020)
Malaysia is one of the most rapidly developing countries among developing nations. The construction industry has played a major role in Malaysia’s rapid economic growth. Among the major sectors in Malaysia, the importance of the construction industry is unique regardless of the level of the country’s development. However, the attitude of the construction industry in Malaysia towards managing contractors’ risk attitudes is very weak. The introduction of the Occupational Safety and Health Act in 1994 by the Malaysian government made all industries in Malaysia to identify risks, conduct risk assessment and control risk. In addition, the Malaysian construction industry simultaneously implemented an integrated system to ensure consistency and better performance of projects. To identify the factors influencing contractors' risk attitudes, relevant literature was reviewed, and a questionnaire survey was conducted. This study focused on the G7 contractors operating in the Malaysian construction industry. One hundred and nineteen copies of a structured questionnaire were analysed with a response rate of 85%. Structural equation modelling was utilized to test the hypotheses developed for the study. Results showed that government policies played a moderating role in enhancing the relationship between human-related factors affecting contractors’ risk attitudes in the construction industry.